Analisis Kesalahan Siswa Dalam Menyelesaikan Soal-Soal Matematika Materi Persamaan Garis Lurus Berdasarkan Prosedur Newman - Maria A. Maluwu; Vivian E. Regar; Jorry F. Monoarfa (Journal on Education, 2024)
Students' abilities in solving mathematical problems need to be improved. Many students still need help solving mathematical problems, especially story problems. This research analyses students' errors in solving mathematics problems using the Newman procedure on straight-line equations. The research method used is qualitative research. The data collection techniques used were tests and interviews. Meanwhile, data analysis techniques use qualitative data presentation, data reduction, and conclusion. The conclusions obtained include: (1) reading errors with a percentage of 3%, which is classified as very low; (2) comprehension errors with a percentage of 10%, which is classified as very low; (3) Transformation errors with a percentage of 14% which is classified in the deficient category, (4) Process skill errors with a percentage of 38% which are classified as low category, (5) Final answer writing errors with a percentage of 18% which are classified as deficient category